2010
DOI: 10.1093/sleep/33.5.601
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and Health Correlates of Sleep Quality and Duration among Very Old Chinese

Abstract: Study Objectives: To examine factors associated with self-reported sleep quality and duration among very old adults in China. Design: Cross-sectional analysis of the 2005 wave of the Chinese Longitudinal Healthy Longevity Survey (CLHLS). Setting: In-home interview with older adults in 22 provinces in mainland China. Participants: A total of 15,638 individuals aged 65 and older (5,047 aged 65-79, 3,870 aged 80-89, 3,927 aged 90-99, and 2,794 aged 100 and older, including 6,688 men and 8,950 women). Intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
134
8
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(164 citation statements)
references
References 49 publications
(92 reference statements)
17
134
8
5
Order By: Relevance
“…This duration seemed longer than that found in other studies, with a mean of 7 -7.5 h and a larger group (≥30%) with short sleep duration. 6,19 Consistent with other studies, 3,17 depression, cognitive impairment, lack of social cohesion and moderate or severe activity limitations were associated with a current sleeping problem. Depression has been found in several studies to be a risk factor for sleep disturbances.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This duration seemed longer than that found in other studies, with a mean of 7 -7.5 h and a larger group (≥30%) with short sleep duration. 6,19 Consistent with other studies, 3,17 depression, cognitive impairment, lack of social cohesion and moderate or severe activity limitations were associated with a current sleeping problem. Depression has been found in several studies to be a risk factor for sleep disturbances.…”
Section: Discussionsupporting
confidence: 83%
“…Depression has been found in several studies to be a risk factor for sleep disturbances. 33,34 Unlike in certain other studies, 3,6,7,[9][10][11][12]14 gender, age, socioeconomic status, population group, urban residence, health behaviour (tobacco use, alcohol use and physical activity) and chronic conditions were not found to be associated with sleeping problems.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…However, this conclusion is not in agreement with other studies. Gu et al (2010) found that quality of sleep of the very elderly did not differ substantially from that of the young elders. Tafaro et al (2007) also reported that long-lived individuals showed better self-rated sleep quality.…”
Section: Discussionmentioning
confidence: 85%
“…Tafaro et al (2007) also reported that long-lived individuals showed better self-rated sleep quality. This disagreement could be explained by the following factors: (1) these two studies (Gu et al 2010;Tafaro et al 2007) used self-rated quality of sleep, which is a subjective measurement; (2) the participants included in these two studies were healthier than those included in our study; and (3) the healthy long-lived participants might have their own perception of what is "acceptable" sleep and, therefore, did not report poor sleep quality even if objective quality of sleep does in fact change with advancing age.…”
Section: Discussionmentioning
confidence: 99%